Incidence of sinus thrombosis with thrombocytopenia-A nation-wide register study. - Petteri Hovi; Arto A Palmu; Tuomo A Nieminen; Miia Artama; Jukka Jokinen; Esa Ruokokoski; Riitta Lassila; Hanna Nohynek; Terhi Kilpi (PLoS ONE, 2023)
Safe vaccination is essential for mitigation of the COVID-19 pandemic. Two adenoviral vector vaccines, ChAdOx1 nCov-19 (AstraZeneca) and Ad26.COV2.S (Johnson&Johnson/Janssen) have shown to be effective and they are distributed globally, but reports on serious cerebral venous sinus thrombosis (CVST) associated with thrombocytopenia, have emerged. Our objective was to evaluate the background incidence of CVST with thrombocytopenia and to compare it to incidences following COVID-19 vaccines. We conducted a register-based nation-wide cohort study in Finland, including all 5.5 million individuals alive in Finland, 1 Jan 2020. COVID-19 vaccinations registered in the National Vaccination Register served as the exposure. We detected CVST admissions or hospital visits recorded in the hospital discharge register from Jan 1, 2020 through April 2, 2021. We confirmed the diagnosis of CVST and thrombocytopenia (platelet count <150,000 per cubic millimeter) using radiology reports and laboratory data. By Poisson regression, we compared the baseline incidences to the risks within four weeks after COVID-19 vaccinations. Out of the 167 CVST episodes identified in the registers, 117 were confirmed as CVST, 18 of which coincided with thrombocytopenia (baseline incidence 0.18 per 28 days per million persons). We found 2 episodes of CVST with thrombocytopenia within 28 days of the first ChAdOx1 nCov-19 vaccination (among 200,397 vaccinated, aged 16 or above). No cases were found following the first mRNA vaccine dose among 782,604 vaccinated. The background incidence of CVST combined with thrombocytopenia was minuscule compared to the incidence during the weeks following the ChAdOx1 nCov-19 vaccination. Accurate estimation of the baseline incidence is essential in the critical appraisal of the benefit-risk of any vaccination program.